PELATIHAN PRAKTIKUM SEDERHANA BERBASIS KIMIA HIJAU UNTUK GURU-GURU KABUPATEN OGAN ILIR SUMATERA SELATAN - Sofia Sofia; Muhammad Hadeli L; Rodi Edi; Diah Kartika Sari; Maefa Eka Haryani; Eka Ad'hiya (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
Green chemistry is an alternative solution that can be used by chemistry teachers for safe and environmentally friendly chemistry experiments in schools. This community service aims to provide training to high school/vocational high school chemistry teachers in Ogan Ilir Regency, South Sumatra to carry out simple practical activities based on green chemistry. This service activity consists of 3 main stages, namely the preparation stage, the implementation stage and the evaluation stage. The target audience for this community service activity are 24 high school chemistry teachers from Ogan Ilir, South Sumatra. And furthermore, it is hoped that chemistry teachers who attend training can guide their chemistry teacher colleagues in their place. There are 7 simple green chemistry-based practical procedures collected from this service activity. The simple green chemistry-based practicum procedures are: 1) Redox reactions; 2) Making Binahong Covid-19 Herbal Soap; 3) Factors Affecting Reaction Rate; 4) Colloid-Tofu Making; 5) Colloids - Clumping (Coagulation) of Colloidal Particles; 6) Combustion of carbon compounds (complete and incomplete combustion); 7) Freezing Rubber Sap Using Pineapple Peel Extract. Overall, the target audience has been trained to make simple practical procedures based on green chemistry. This can be seen from the materials and practicum procedures that are in accordance with the basic principles of green chemistry, namely environmentally friendly, reducing environmental pollution, not classified as hazardous materials.